Examining the Development-Security Nexus: Historical Analogies and Nation Building in U.S. Foreign Policy - Laub, Zachary J. (Tufts Archival Research Center, 2005)
Policymakers frequently invoke historical analogies in rhetoric to advocate for or justify their foreign policy agendas. Some political scientists have observed that policymakers often rely on these same historical analogies to diagnose and analyze foreign policy situations, and draw inferences and policy prescriptions. To what extent have these presumptive "lessons of the past" informed the formulation, implementation, and evaluation of nation building campaigns? I turn to a case study of the Alliance for Progress to investigate the role of analogical reasoning in the decision making process. The Alliance, John F. Kennedy_ï¿½_s development program in Latin America, was in many ways a prototype of the "hearts and minds" approach to counterinsurgency. Drawing largely on archival sources, I trace the use of the Marshall Plan analogy in the administration's decision making. I find that reasoning by historical analogy was not determinative of policy outcomes. Rather, domestic politics in both the U.S. and host countries placed the biggest constraints on the Alliance, whose outcomes were underwhelming and at times perverse. However, reasoning by historical analogy may have affected decision making at the margins, particularly by shaping policymakers' prognoses of the program. Analogies contemporaneous to the Marshall Plan "the reconstruction of Germany and Japan" were ubiquitous in the occupation of Iraq. As archival materials from the Bush administration are opened to researchers, this may provide a useful case to confirm or refine the arguments made here regarding the impacts of analogical reasoning on policy. I conclude with a discussion of methods and prospects for the more prudential use of history in foreign policy decision making.